Implementasi Kurikulum Merdeka Belajar pada Pembelajaran Pendidikan Agama Islam di Sekolah Menengah Pertama - Susanti, Weti; Khadafi, Muhammad; Rahman, Abd.; Rahmi, Azvi; Sobri, Sobri; Fatimah, Fatimah; Vanessa, Anadya Diva (Al-Hashif: Jurnal Pendidikan dan Pendidikan Islam, 2023)
This study aims to find out: 1. Planning, 2. Implementation, and 3. Evaluation of the Independent Learning Curriculum in Islamic Education Subjects at Junior High School. The research method is field research (field research) which is descriptive in nature, namely describing the facts as they are from the results the research obtained was in accordance with the problems under study, and the primary data source was the Islamic Education teacher, and the secondary data source was the Madrasah head and 3 class VII students using the Purposive Teacher Islamic Education Technique. Data collection techniques used in this study are observation, interviews, and documentation studies. Managing data through data reduction steps, data presentation, and drawing conclusions/data verification. Related research results 1. Planning, 2. Implementation, and 3. Learning evaluation of the independent curriculum learning The objectives of the independent curriculum have been achieved in Islamic Education learning at Junior High School that have been achieved but not so perfectly that it can be said that 75% of the final results are because this curriculum has just been implemented and only implemented learn and there are no guidelines that can be followed, the results are not optimal, so that the maximum goal of the National Education is always to provide training to teachers so they can get maximum results.